2010
DOI: 10.1159/000301586
|View full text |Cite
|
Sign up to set email alerts
|

Flap Anchoring Following Primary Breast Cancer Surgery Facilitates Early Hospital Discharge and Reduces Costs

Abstract: Background: Routine drain placement after breast cancer surgery is standard practice. Anchoring the axillary and mastectomy flaps to the underlying chest wall with sutures has been advocated as a means of avoiding drainage following breast surgery. This study compares outcomes following flap fixation or routine drain placement and uniquely considers the economic implications of each technique. Patients and Methods: Data on seroma formation and wound infection following mastectomy and axillary clearance were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 18 publications
2
48
1
4
Order By: Relevance
“…Halsted first advocated creating a short superior flap and suturing it with interrupted silk to the fascia below the first rib and skin grafting the remaining part of the defect [29]. In 1951, Orr [30] used tension sutures tied over rubber tubing bolsters to tack flaps to the chest wall.…”
Section: Obliteration Of Dead Spacementioning
confidence: 99%
“…Halsted first advocated creating a short superior flap and suturing it with interrupted silk to the fascia below the first rib and skin grafting the remaining part of the defect [29]. In 1951, Orr [30] used tension sutures tied over rubber tubing bolsters to tack flaps to the chest wall.…”
Section: Obliteration Of Dead Spacementioning
confidence: 99%
“…Some studies have demonstrated that dead space under the skin will result in seroma formation and seroma may lead to unwanted complications. [15][16][17] Although the relationship between compression and seroma formation is controversial, we expect that the compression does have a role in reducing seroma-related complications by obliterating the dead space of the flap with appropriate pressure. 18,19 In our experience, we note increased discharge from the flap margins when compression is applied early, supporting our notion.…”
Section: Discussionmentioning
confidence: 99%
“…Halsted first advocated creating a short superior flap and suturing it with interrupted silk to the fascia below the first rib and skin grafting the remaining part of the defect. [29] In 1951, Orr [30] used tension sutures tied over rubber tubing bolsters to tack flaps to the chest wall. In 1953, Keyes et al [31] used through and through sutures to attach the skin flaps to the chest wall.…”
Section: Management Of Dead Spacementioning
confidence: 99%